E-sampah: The administrative solution for the waste bank in Politeknik Negeri Samarinda - Muhammad Aji Pangestu; Karyo Budi Utomo; Marlinda Marlinda; Ahyar Muhammad Diah; Ramadhan Dhimas Tasmara; Razfi Nursyah; Zahiratul Mujaahidah; Noversi Allo Layuk (Universitas Muhammadiyah Magelang, 2023)
The waste bank of Politeknik Negeri Samarinda has problems recording transactions, both discrepancies, writing errors, illegible writing and repeated recording. This is because the operation still uses conventional techniques. So the purpose of this e-Sampah program is to make it easier for waste banks and their customers to collect data on waste deposits that can be monitored and reported automatically. By designing using the PHP and MySql programming languages, this activity was carried out in November 2022 at the waste bank of Politeknik Negeri Samarinda. The method used is making e-Sampah applications, application trials, outreach and training related to how to operate e-Sampah applications. With the existence of e-Sampah, the problems complained of by the waste bank management were resolved. In addition, this activity also supports the waste bank program towards going digital.